Knowledge-based view as a foundation for competitive advantage : Improving competitive advantage with thought leadership - Karvonen, Lauri (My University, 2019)
The purpose of this study is to investigate whether there is a connection between thought leadership point-of-view posts in social media and the engagement rates social media posts receive on different social media channels. The theoretical background for this study comes from the knowledge-based view, where companies' competitive advantage is based on the knowledge their employees hold and how well that knowledge can be utilized to create a competitive advantage. The theoretical part of this study provides insights into the knowledge creation process and how to start building knowledge-based organizations, what are the key factors behind achieving a competitive advantage, and how to build a thought leadership strategy. This study was conducted using a content analysis method. Three business-to-business design con-sultancy companies’ social media posts content were analyzed, and from there conclusions were made. The social media channels used in this study were Twitter, LinkedIn, and Facebook. A total of 45 posts were analyzed (15 per company and per channel). The results show that there is a strong connection between thought leadership point-of-view posts and higher engagement rates. On both Twitter and LinkedIn, 80% of the posts (12 out of 15) were consid-ered to be thought leadership posts. On Facebook, the number was 73% (11 out of 15 posts). Looking at the results, thought leadership is a very credible way to gain a competitive advantage. It is something that companies should consider incorporating in its strategies to better serve its customers, increase its internal knowledge capabilities, and gain a competitive advantage over its competition.

Tämän tutkimuksen tarkoituksena on selvittää, onko sosiaalisessa mediassa jaettujen ajatusjohtajuus-viestien ja niiden saamien sitoutumisasteiden (eng. engagement rate) välillä yhteys. Tämän tutkimuksen teoreettinen tausta perustuu tietopohjaiseen näkemykseen (eng. knowledge-based view), jossa yritysten kilpailuetu rakentuu yksittäisten työntekijöiden olemassa olevaan tietoon ja sii-hen, kuinka hyvin tätä tietoa voidaan hyödyntää kilpailuedun luomisessa. Tämän tutkimuksen teoreet-tinen osa tarjoaa näkökulmia tiedon luomisprosessin sekä siihen miten tietopohjaista organisaatiota voidaan lähteä rakentamaan, mitkä ovat avaintekijöitä kilpailuedun saavuttamisessa ja kuinka rakentaa ajatusjohtajuusstrategiaa. Tämä tutkimus suoritettiin sisällönanalyysimenetelmällä. Kolmen business-to-business design-konsultointi yrityksen sosiaalisen median viestien sisältöjä analysointiin, ja sen pohjalta tehtiin johto-päätökset. Tässä tutkimuksessa käytetyt sosiaalisen median kanavat olivat Twitter, LinkedIn ja Face-book. Kaikkiaan 45 viestiä analysointiin (15 per yritys ja kanava). Tulokset osoittavat, että ajatusjohtamisen näkökulmasta lähetettyjen viestien ja korkeampien sitoutu-misasteiden välillä on vahva yhteys. Sekä Twitterissä että LinkedInissä 80 prosenttia viesteistä (12:sta 15:sta) katsottiin olevan ajatusjohtajuussisältöä. Facebookissa määrä oli 73% (11 viestiä 15:sta). Tuloksista on pääteltävissä, että ajatusjohtaminen on erittäin uskottava tapa saavuttaa kilpailuetua. Jotta yritykset voivat palvella paremmin asiakkaitaan, kasvattaa sisäisiä tietojaan ja saavuttaa kilpailuetua kilpailijoihinsa nähden, on ajatusjohtajuus jotain, jota niiden tulisi harkita osaksi strategiaansa.
Keywords: Thought leadership, knowledge-based view, competitive advantage